Social housing development in the Arabian Gulf countries: policies, practices, and prospects - Zairul, Mohd (Frontiers in Built Environment, 2025)
The Arabian Gulf has witnessed rapid social housing transformations driven by modernization, economic diversification, and ambitious policy reforms such as Saudi Arabia’s Vision 2030. Despite these efforts, persistent issues of affordability, regulatory inefficiency, and socio-cultural misalignment continue to challenge sustainable housing delivery. Current reviews are fragmented, often focusing narrowly on policy or technology, with limited integration of cultural and participatory dimensions. This gap highlights the need for a systematic synthesis that captures the multi-dimensional nature of housing development in the Gulf. This review aims to provide a comprehensive analysis of social housing development in the Arabian Gulf, examining the interplay of policies, cultural dynamics, technological practices, and participatory design approaches. Employing the Thematic Review (TreZ) method, which integrates systematic coding and synthesis through ATLAS.ti, 26 peer-reviewed empirical studies published between 2020 and 2025 were analyzed to identify recurring patterns and emerging themes. The analysis generated four dominant themes: (1) Government policies and economic drivers, emphasizing Vision 2030, PPPs, and affordability reforms; (2) Cultural and demographic impacts, including privacy, gender segregation, and household size; (3) Technological and sustainable practices, highlighting green roofs, BIM, AI, MMC, and Industry 4.0 tools; and (4) Participatory design and socio-cultural sustainability, addressing the neglect of cultural heritage and the potential of VR-enabled engagement. Findings indicate that while Gulf states are pursuing progressive, innovation-driven housing policies, critical gaps remain in socio-cultural sustainability and methodological integration. This research benefits scholars, policymakers, and practitioners by offering a holistic framework for advancing resilient, inclusive, and contextually grounded housing models in the Arabian Gulf.